Establishment of a long-term secondary lymphedema animal model in the rodent hindlimb - Yoon, Sung-Hwan; Suh, Hyun Suk Peter; Yoon, Jin-Hui; Cho, Hayeong; Myung, Yujin; Jeon, Jae Yong (Frontiers in Surgery, 2026)
IntroductionSecondary lymphedema is a chronic swelling of the extremities caused by physical disruption of the lymphatic system, leading to impaired lymph drainage. It frequently develops in cancer patients after surgical removal of lymph nodes and vessels during tumor resection, when reconnection of lymphatic pathways fails. Current clinical therapies are mainly palliative or conservative, with limited therapeutic effects. Therefore, an animal model that closely mimics the chronic and severe characteristics of secondary lymphedema in patients is required to enable mechanistic and therapeutic research.MethodsTo establish a long-term secondary lymphedema model in the mouse hindlimb, a combination of surgical, radiological, and mechanical interventions was designed. A novel surgical procedure termed the folding suture technique was developed to disrupt both the superficial and deep lymphatic networks. Controlled radiation exposure was applied postoperatively to inhibit early-stage lymphangiogenesis, while hindlimb immobilization was introduced to suppress lymphatic pumping and enhance edema formation.ResultsThe newly developed model showed a significant and persistent increase in hindlimb paw thickness, with edema sustained for over six weeks. Immunofluorescence analysis demonstrated a markedly reduced number and diameter of regenerated lymphatic vessels compared to previously established models. Functional lymphography using fluorescein isothiocyanate (FITC)-dextran and live indocyanine green (ICG) imaging confirmed diminished lymphangiogenesis and impaired lymphatic flow. Further evaluation using the leg dermal backflow (LDB) staging system—commonly applied in clinical assessment—showed consistently higher severity scores, indicating a robust and irreversible secondary lymphedema phenotype.DiscussionThis study demonstrates that the newly established mouse hindlimb lymphedema model successfully replicates the chronic, severe, and irreversible nature of clinical secondary lymphedema. The combination of the folding suture technique, radiation-induced inhibition of lymphangiogenesis, and immobilization effectively induces and maintains the pathology. This model provides a reliable preclinical platform for in-depth investigation of secondary lymphedema pathophysiology and for the development and validation of novel therapeutic strategies.